Gottfried Haberler: Contributions upon Entering his Ninth Decade - Gillis, Malcolm (Quarterly Journal of Economics, 1982)
Journal Article Gottfried Haberler: Contributions upon Entering his Ninth Decade Get access Malcolm Gillis Malcolm Gillis Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 97, Issue 1, February 1982, Pages 139–140, https://doi.org/10.2307/1882630 Published: 01 February 1982